Preparation method of side chain type liquid crystal photosensitive resin monomer with photo-orientation heat conduction anisotropy and application of side chain type liquid crystal photosensitive resin monomer in 3D printing
Through the introduction of the side chain LCD structure in the light -sensitive resin, the orderly arrangement of LCD molecules under the action of light is used to solve the problem of insufficient thermal thermal conductivity of light -sensitive tree lipids. Insulation packaging of equipment.
Patent Information
- Application Number
- CN202411360520.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing photosensitive resin has low thermal conductivity and is difficult to meet the heat dissipation needs of insulated packaging of high-power, ultra-high frequency microelectronic devices and high-voltage power equipment.
By introducing the side chain liquid crystal structure, prepare the light -based LCD optical resin monomer of the opposite sex, and apply the material in 3D printing. The liquid crystal molecule is used to form a highly orderly crystalline structure under the action of light to improve the thermal conductivity. performance.
实现了3D打印制品在某些方向上的显著提高导热率和拉伸强度,表现出各向异性的特征,能够更有效地满足高性能电子设备的散热需求。
Smart Images

Figure CN119371336A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a method for preparing a side-chain liquid crystal photosensitive resin monomer with light-orienting and thermally anisotropic properties and an application thereof in 3D printing. Background Art
[0002] With the development of modern artificial intelligence, the requirements for electronic devices are getting higher and higher, among which thermal management has become an important factor affecting the performance of electronic devices. Polymer materials are widely used in the protection and packaging of electronic devices due to their light weight, easy processing, chemical corrosion resistance and low cost. However, their poor intrinsic thermal conductivity often limits their application depth.
[0003] Photosensitive resins are widely used in insulation fields such as electrical equipment due to their excellent adhesion, electrical insulation, corrosion resistance and excellent processing and molding properties. However, the thermal conductivity of photosensitive resins is also low, so it is difficult to adapt to the heat dissipation requirements of insulating packaging of high-power, ultra-high frequency microelectronic devices and high-voltage power equipment. At present, like other common polymers, the research on the thermal conductivity of photosensitive resins mainly involves the following two aspects: one is to add a large amount of thermally conductive particles to prepare filled photosensitive resins; the other is to synthesize intrinsic thermally conductive polymers with high thermal conductivity. Although the method of filling with thermally conductive particles is simple and effective, for photosensitive resins, in order to achieve higher thermal conductivity, the amount of thermally conductive filler added needs to reach a certain percolation threshold. However, the higher amount of filler added affects the 3D printing molding performance of photosensitive resins. Therefore, the second method of preparing intrinsic thermally conductive photosensitive resins can be coordinated with the first method to a certain extent to improve the thermal conductivity of photosensitive resin materials.
[0004] Liquid crystal molecules tend to form highly ordered crystalline structures due to their molecular orientation, which greatly increases the free path of phonon transmission and reduces phonon scattering, thus having good thermal conductivity. Therefore, introducing a liquid crystal unit structure is an effective method to improve the thermal conductivity of polymers. Gu Junwei et al. prepared an intrinsic high thermal conductivity epoxy resin with a liquid crystal unit structure, and the liquid crystal structure significantly improved the thermal conductivity of the epoxy resin (CN 113234042 A). In addition, there are many patent applications for using liquid crystal units to improve the thermal conductivity and strength of resins (CN 113881006B, CN 114058155 B, CN 113604007 B, CN 108409689 B, and CN 111205249 B, etc.). This research team previously studied the effect of liquid crystal structure on the performance of 3D printing photosensitive resins, and found that liquid crystal units can be oriented with the action of light in 3D printing to form anisotropic structures, and 3D printed products show anisotropic characteristics (CN 117551238 A). Patent application CN 116969840 A prepares an acrylic resin liquid crystal monomer, which is oriented under the action of an electric field and shaped under photopolymerization to obtain an intrinsic high thermal conductivity liquid crystal material in the lateral direction. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a side-chain liquid crystal photosensitive resin monomer with photo-orientation and thermal conductivity anisotropy and its application in 3D printing.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The side chain type liquid crystal photosensitive resin monomer with light orientation and thermal conductivity anisotropy has a structure as shown in Formula I:
[0008]
[0009] The preparation steps of the side chain type liquid crystal photosensitive resin monomer are as follows:
[0010] (1) 2,2-di(hydroxymethyl)propionic acid and 2,2-dimethoxypropane are dissolved in acetone, and then p-toluenesulfonic acid is added to the above solution. The resulting mixture is reacted for 12 to 18 hours under stirring at room temperature, and then triethylamine is added and reacted for 5 to 10 minutes. Finally, the acetone is removed by rotary evaporation at 75 to 85° C., and the obtained residue is dissolved in dichloromethane, and then the mixture is washed with Na2CO3 and distilled water respectively, and the organic phase is dried with anhydrous Na2SO4, and then the dichloromethane is removed by rotary evaporation to obtain a white solid product 1;
[0011] (2) The white solid product 1 and 4-phenylphenol are dissolved in tetrahydrofuran to obtain a solution, which is cooled to 0-5° C., dicyclohexylcarbodiimide and 4-dimethylaminopyridine are dissolved in tetrahydrofuran and then slowly added to the solution, the resulting mixture is reacted for 12-18 hours under stirring, and then the tetrahydrofuran is removed by rotary evaporation, the obtained residue is dissolved in dichloromethane, and then the mixture is washed with NaHCO3 and distilled water respectively, the organic phase is dried with anhydrous Na2SO4, and then the dichloromethane is removed by rotary evaporation to obtain a white solid product 2;
[0012] (3) dissolving the product 2 in methanol, adding ion exchange resin, reacting at room temperature for 12 to 18 hours, filtering off the ion exchange resin, and removing the methanol by rotary evaporation to obtain a transparent liquid product 3;
[0013] (4) The transparent liquid product 3 is diluted with tetrahydrofuran, isophorone diisocyanate is added, dibutyltin dilaurate as a catalyst is added, the mixture is reacted at 75 to 85° C. for 5 to 9 hours, tetrahydrofuran is removed by rotary evaporation to obtain a light yellow viscous liquid, the obtained light yellow viscous liquid is dissolved in ethyl acetate, hydroxyethyl methacrylate is added, dibutyltin dilaurate as a catalyst is added, the mixture is reacted at 85 to 95° C. for 5 to 8 hours, the ethyl acetate solvent is removed by rotary evaporation to obtain a light yellow viscous side chain liquid crystal photosensitive resin monomer.
[0014] The molar ratio of the 2,2-di(hydroxymethyl)propionic acid to 2,2-dimethoxypropane is 1:(1-1.5).
[0015] The molar ratio of the product 1 to 4-phenylphenol is 1:(1-1.2).
[0016] The molar ratio of the product 2 to the ion exchange resin is 1:(1-1.2).
[0017] The molar ratio of the product 3 to IPDI (isophorone diisocyanate) is 1:(2-2.4).
[0018] The molar ratio of the product 3 to HEMA (hydroxyethyl methacrylate) is 1:(2-2.4).
[0019] The present invention also provides an intrinsic high thermal conductivity liquid crystal photosensitive resin material, which is composed of the side chain type liquid crystal photosensitive resin monomer, a diluent DMAA (N,N-dimethylacrylamide), a photoinitiator TPO (trimethylbenzoyl-diphenylphosphine oxide), and a photoinitiator 184 (1-hydroxycyclohexyl phenyl acetone), and the formula thereof is as follows in parts by weight:
[0020]
[0021] The intrinsic high thermal conductivity liquid crystal photosensitive resin material is applied to the 3D printing process as follows: N, N-dimethylacrylamide and side chain liquid crystal photosensitive resin monomer are mixed evenly under high-speed stirring, and then 2, 4, 6-trimethylbenzoyl-diphenylphosphine oxide and 1-hydroxycyclohexyl phenyl ketone are added, stirred until the mixed solution is clear, poured into the resin tank of the photosensitive resin 3D printer for light-curing 3D printing, the wavelength of the light is preferably 405nm, and the illumination time is preferably 6 to 12s.
[0022] In order to utilize the orientation property of liquid crystal units under the action of light, the present invention introduces liquid crystal units as side chains into the photosensitive resin structure, prepares side chain liquid crystal photosensitive resin monomers and applies them to 3D printing. Compared with the existing technology, the present invention has the following advantages:
[0023] 1. The side chain liquid crystal structure is oriented under the action of the 3D printing laser to form a highly ordered crystalline structure, which exhibits good thermal conductivity in the orientation direction, making the 3D printed product have anisotropic thermal conductivity.
[0024] 2. The rigid liquid crystal unit gives the photosensitive resin good mechanical properties and temperature resistance. Therefore, the side-chain liquid crystal photosensitive resin monomer with anisotropic light orientation and thermal conductivity of the present invention has good mechanical properties after 3D printing. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The figure is the nuclear magnetic hydrogen spectrum of the chain-type liquid crystal photosensitive resin monomer of the present invention.
[0026] Figure 2 These are polarizing microscope (POM) photos of the side chain type liquid crystal photosensitive resin monomer of the present invention at different temperatures. DETAILED DESCRIPTION
[0027] In order to further explain the technical solution of the present invention, the present invention is described in detail below through specific embodiments.
[0028] Example 1
[0029] According to molar amount, 1 mol of 2,2-di(hydroxymethyl)propionic acid and 1.2 mol of 2,2-dimethoxypropane were dissolved in acetone, and then 0.01 mol of p-toluenesulfonic acid was added to the above solution, and the mixture was stirred at room temperature for 9 hours. Then 0.01 mol of triethylamine was added, and after reacting for 5 minutes, the acetone was removed by rotary evaporation, and the obtained residue was dissolved in dichloromethane, and then the mixture was washed with Na2CO3 and distilled water respectively, and the organic phase was dried with anhydrous Na2SO4, and then the dichloromethane was removed by rotary evaporation to obtain 2,2-di(hydroxymethyl)propionic acid protected by terminal hydroxyl groups.
[0030] Dissolve 1 mol of hydroxy-terminated 2,2-di(hydroxymethyl)propionic acid and 1.1 mol of 4-phenylphenol in tetrahydrofuran, cool to 0°C, and slowly add a tetrahydrofuran solution containing 0.005 mol of dicyclohexylcarbodiimide and 0.005 mol of 4-dimethylaminopyridine. Stir and react for 12 hours. Remove tetrahydrofuran and dicyclohexylcarbodiimide by rotary evaporation, dissolve the obtained residue in dichloromethane, and then wash the mixture with NaHCO3 and distilled water respectively, dry the organic phase with anhydrous Na2SO4, and then remove dichloromethane by rotary evaporation to obtain a side chain liquid crystal product protected by a hydroxy-terminated side chain.
[0031] 1 mol of the terminal hydroxyl-protected side chain liquid crystal was dissolved in methanol, and ion exchange resin Amberlite IR-120 was added. After reacting at room temperature for 12 hours, the ion exchange resin was filtered and the methanol was removed by rotary evaporation to obtain a terminal hydroxyl-protected side chain liquid crystal product.
[0032] 1 mol of terminal hydroxyl side chain liquid crystal product was dissolved in tetrahydrofuran, 2.2 mol of isophorone diisocyanate was added to the above solution, 0.001 mol of organic tin catalyst dibutyltin dilaurate was added, the reaction was carried out at 75°C for 6 hours, and the tetrahydrofuran was removed by rotary evaporation to obtain a light yellow viscous liquid, the obtained light yellow viscous liquid was dissolved in ethyl acetate, 2.3 mol of hydroxyethyl methacrylate was added, 0.001 mol of catalyst dibutyltin dilaurate was added, the reaction was carried out at 90°C for 6 hours, and the tetrahydrofuran was removed by rotary evaporation to obtain a light yellow side chain liquid crystal photosensitive resin monomer.
[0033] By weight, 60 parts of side chain liquid crystal photosensitive resin monomer, 40 parts of N,N-dimethylacrylamide, 4 parts of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 1 part of photoinitiator 1-hydroxycyclohexyl phenyl ketone were stirred until the mixed solution was clear, and then poured into the resin tank of the photosensitive resin 3D printer for light curing 3D printing. The wavelength of the light was 405nm and the illumination time was 9s. The thermal conductivity test and mechanical properties samples were printed longitudinally and transversely respectively.
[0034] Example 2
[0035] The side chain type liquid crystal photosensitive resin monomer was prepared according to the method shown in Example 1.
[0036] According to weight, 70 parts of side chain liquid crystal photosensitive resin monomer, 30 parts of N,N-dimethylacrylamide, 4 parts of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 1 part of photoinitiator 1-hydroxycyclohexyl phenyl ketone were stirred until the mixed solution was clear, and then poured into the resin tank of the photosensitive resin 3D printer for light curing 3D printing. The wavelength of the light was 405nm and the illumination time was 9s. The thermal conductivity test and mechanical properties samples were printed using the longitudinal and transverse methods respectively.
[0037] Example 3
[0038] The side chain type liquid crystal photosensitive resin monomer was prepared according to the method shown in Example 1.
[0039] By weight, 80 parts of side chain liquid crystal photosensitive resin monomer, 20 parts of N,N-dimethylacrylamide, 4 parts of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 1 part of photoinitiator 1-hydroxycyclohexyl phenyl ketone were stirred until the mixed solution was clear, and then stirred until the mixed solution was clear, poured into the resin tank of the photosensitive resin 3D printer for light curing 3D printing, the wavelength of the light was 405nm, and the illumination time was 9s. The thermal conductivity test and mechanical properties samples were printed using the longitudinal and transverse methods respectively.
[0040] Example 4
[0041] The side chain type liquid crystal photosensitive resin monomer was prepared according to the method shown in Example 1.
[0042] By weight, 90 parts of side chain liquid crystal photosensitive resin monomer, 10 parts of N,N-dimethylacrylamide, 4 parts of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 1 part of photoinitiator 1-hydroxycyclohexyl phenyl ketone were stirred until the mixed solution was clear, and then poured into the resin tank of the photosensitive resin 3D printer for light curing 3D printing. The wavelength of the light was 405nm and the illumination time was 9s. The thermal conductivity test and mechanical properties samples were printed longitudinally and transversely respectively.
[0043] Comparative Example 1
[0044] By weight, 100 parts of bisphenol A epoxy resin, 3 parts of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 1 part of photoinitiator 1-hydroxycyclohexyl phenyl ketone were stirred until the mixture was clear, and then poured into the resin tank of the photosensitive resin 3D printer for light-curing 3D printing. The wavelength of the light was 405nm and the illumination time was 9s. The thermal conductivity test and mechanical properties samples were printed longitudinally and transversely respectively.
[0045] Comparative Example 2
[0046] By weight, 100 parts of commercial acrylic photosensitive resin, 3 parts of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 1 part of photoinitiator 1-hydroxycyclohexyl phenyl ketone were stirred until the mixed solution was clear, and then poured into the resin tank of the photosensitive resin 3D printer for light-curing 3D printing. The wavelength of the light was 405nm and the illumination time was 9s. The thermal conductivity test and mechanical properties samples were printed longitudinally and transversely respectively.
[0047] In accordance with the national test standard GB / T 1040.1-2018, the corresponding tensile test specimens were printed using the Form 2 3D printer. The tensile test was carried out using the LD24 electronic universal material testing machine; the loading rate during the tensile test was set to 10mm / min. In accordance with the international general thermal conductivity test standard ASTM-D5470, the thermal conductivity of the intrinsic high thermal conductivity liquid crystal photosensitive resin material obtained was tested using the Xiangtan Xiangyi thermal conductivity tester DRL-III.
[0048] Table 1 Thermal conductivity and tensile strength of printed products
[0049]
[0050] It can be seen from Table 1 that with the introduction of the side chain liquid crystal structure, the thermal conductivity of the 3D photocured product is improved to a certain extent, among which with the increase of the content of the side chain liquid crystal structure, the thermal conductivity in the thickness direction of the transverse printed product is significantly improved. The thermal conductivity of the transverse printed product in Example 4 reaches 0.281W / (m·K), which is about 50% higher than that of Comparative Examples 1 and 2 that do not contain side chain liquid crystal structures. This is because the highly ordered arrangement of liquid crystal molecules in the process of photocuring can form a local crystalline structure, so that the heat flow propagates along the direction of the ordered molecular chain, and can effectively suppress the scattering of phonons, thereby greatly improving the thermal conductivity of the photosensitive resin. At the same time, it can be found that the introduction of the side chain liquid crystal structure has a similar trend on the tensile strength of the 3D printed product, which illustrates the enhancement effect of the side chain liquid crystal structure.
[0051] In summary, the present invention prepares a photosensitive resin monomer by introducing a side chain liquid crystal structure, and applies it to liquid photosensitive resin 3D printing. Since the side chain liquid crystal structure is oriented under the action of the laser in 3D printing to form a local crystalline structure, the 3D printed product has significantly improved thermal conductivity and tensile strength in the direction of these crystal orientations, and exhibits anisotropic characteristics.
[0052] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A side-chain liquid crystal photosensitive resin monomer with light-orienting and thermally anisotropic properties, characterized in that: Its structural formula is as follows:
2. The method for preparing a side-chain liquid crystal photosensitive resin monomer with light orientation and thermal conductivity anisotropy according to claim 1, characterized in that: It includes the following steps: (1) 2,2-di(hydroxymethyl)propionic acid and 2,2-dimethoxypropane are dissolved in acetone, and then p-toluenesulfonic acid is added to the above solution. The resulting mixture is reacted for 12 to 18 hours under stirring at room temperature, and then triethylamine is added and reacted for 5 to 10 minutes. Finally, the acetone is removed by rotary evaporation at 75 to 85° C., and the obtained residue is dissolved in dichloromethane, and then the mixture is washed with Na2CO3 and distilled water respectively, and the organic phase is dried with anhydrous Na2SO4, and then the dichloromethane is removed by rotary evaporation to obtain product 1; (2) dissolving the product 1 and 4-phenylphenol in tetrahydrofuran to obtain a solution, cooling the solution to 0-5° C., dissolving dicyclohexylcarbodiimide and 4-dimethylaminopyridine in tetrahydrofuran and slowly adding the solution to the obtained mixture under stirring for 12-18 hours, then removing the tetrahydrofuran by rotary evaporation, dissolving the obtained residue in dichloromethane, then washing the mixture with NaHCO3 and distilled water respectively, drying the organic phase with anhydrous Na2SO4, and then removing the dichloromethane by rotary evaporation to obtain the product 2; (3) dissolving product 2 in methanol, adding ion exchange resin, reacting at room temperature for 12 to 18 hours, filtering off the ion exchange resin, and removing methanol by rotary evaporation to obtain product 3; (4) The transparent liquid product 3 is diluted with tetrahydrofuran, isophorone diisocyanate is added, dibutyltin dilaurate as a catalyst is added, the reaction is carried out at 75 to 85° C. for 5 to 9 hours, the tetrahydrofuran is removed by rotary evaporation to obtain a liquid, the obtained liquid is dissolved in ethyl acetate, hydroxyethyl methacrylate is added, dibutyltin dilaurate as a catalyst is added, the reaction is carried out at 85 to 95° C. for 5 to 8 hours, the ethyl acetate solvent is removed by rotary evaporation to obtain a side chain type liquid crystal photosensitive resin monomer.
3. The method for preparing a side-chain liquid crystal photosensitive resin monomer with light-orienting and thermally anisotropic properties according to claim 2, characterized in that: The molar ratio of the 2,2-di(hydroxymethyl)propionic acid to 2,2-dimethoxypropane is 1:1-1.
5.
4. The method for preparing a side-chain liquid crystal photosensitive resin monomer with light-orienting and thermally anisotropic properties according to claim 2, characterized in that: The molar ratio of the product 1 to 4-phenylphenol is 1:1-1.
2.
5. The method for preparing a side-chain liquid crystal photosensitive resin monomer with light-orienting and thermally anisotropic properties according to claim 2, characterized in that: The molar ratio of the product 2 to the ion exchange resin is 1:1-1.
2.
6. The method for preparing a side-chain liquid crystal photosensitive resin monomer with light-orienting and thermally anisotropic properties according to claim 2, characterized in that: The molar ratio of the product 3, isophorone diisocyanate and hydroxyethyl methacrylate is 1:2-2.4:2-2.
4.
7. An intrinsically high thermal conductivity liquid crystal photosensitive resin material, characterized in that: It is composed of the following raw materials in parts by weight:
8. The use of an intrinsic high thermal conductivity liquid crystal photosensitive resin material in 3D printing as claimed in claim 7, characterized in that: N,N-dimethylacrylamide and side chain liquid crystal photosensitive resin monomer are mixed evenly under high-speed stirring, and then 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 1-hydroxycyclohexyl phenyl ketone are added, stirred until the mixed solution is clear, and poured into the resin tank of the photosensitive resin 3D printer for light-curing 3D printing.
9. The use according to claim 8, characterized in that: The wavelength of light in the photocuring 3D printing process is 405nm, and the illumination time is 6 to 12s.
Citation Information
Patent Citations
A biphenyl-type liquid crystal epoxy resin, its preparation method and application
CN108409689B
A side-chain liquid crystal epoxy monomer and its preparation method, and a side-chain liquid crystal epoxy resin
CN111205249B
Discotic liquid crystal epoxy resin monomer and preparation method thereof, and intrinsic high-thermal-conductivity liquid crystal epoxy resin material and preparation method thereof
CN113234042A
A LCPU-modified epoxy resin-based thermally conductive composite material, its preparation method and application
CN113604007B
A liquid crystal polyurethane prepolymer for toughening epoxy resin adhesives, its preparation method and application
CN113881006B